Dosimetric comparision of coplanar versus noncoplanar volumetric modulated arc therapy for treatment of bilateral breast cancers - Avinav Bharati; Satyajeet Rath; Rohini Khurana; Madhup Rastogi; Susama R Mandal; Ajeet Kumar Gandhi; Rahat Hadi; Anoop K Srivastava; Surendra Prasad Mishra (Journal of Medical Physics, 2023)
Introduction: The purpose of this study was to compare the dosimetric parameters of volumetric modulated arc therapy (VMAT) treatment plans using coplanar and noncoplanar beams in patients with bilateral breast cancer/s (BBCs) in terms of organ at risk sparing and target volume coverage. The hypothesis was to test whether VMAT with noncoplanar beams can result in lesser dose delivery to critical organs such as heart and lung, which will result in lesser overall toxicity. Materials and Methods: Data of nine BBC cases treated at our hospital were retrieved. Computed tomography simulation data of these cases was used to generate noncoplanar VMAT plans and the parameters were compared with standard VMAT coplanar plans. Contouring was done using radiation therapy oncology group guidelines. Forty-five Gray in 25 fractions was planned followed by 10 Gy in five fractions boost in breast conservation cases. Results: No significant difference in planning target volume (PTV) coverage was found for the right breast/chestwall (P = 0.940), left breast/chestwall (P = 0.872), and in the total PTV (P = 0.929). Noncoplanar beams resulted in better cardiac sparing in terms of Dmean heart. The difference in mean dose was >1 Gy (8.80 ± 0.28 − 7.28 ± 0.33, P < 0.001). The Dmean, V20 and V30 values for total lung slightly favor noncoplanar beams, although there was no statistically significant difference. The average monitor units (MUs) were similar for coplanar plans (1515 MU) and noncoplanar plans (1455 MU), but the overall treatment time was higher in noncoplanar plans due to more complex setup and beam arrangement. For noncoplanar VMAT plans, the mean conformity index was slightly better although the homogeneity indices were similar. Conclusion: VMAT plans with noncoplanar beam arrangements had significant dosimetric advantages in terms of sparing of critical organs, that is Dmean of heart doses with almost equivalent lung doses and equally good target coverage. Larger studies with clinical implications need to be considered to validate this data.